ANALYSIS OF HEMOGLOBIN LEVELS AND LEUKOCYTE COUNT IN NEONATES WITH HYPERBILIRUBINEMIA - Dewi Suharti; Sulina Yanti Wibawa; Mutmainah Mutmainah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Hyperbilirubinemia is one of the most common clinical phenomena in neonatal patient. Etiology is generally physiological, only about 10% being pathological. It is important for clinicians to distinguish between physiological and pathological hyperbilirubinemia, because uncontrolled pathological conditions can cause severe complications of kern icterus, one ofthe causes of death in infants.This study was retrospective study by obtaining data of all neonatal patients with diagnosis of hyperbilirubinemia, who undergone hemoglobin and leukocyte count test. The data were classified into two groups: physiological and pathological hyperbilirubinemia. Statistical tests were performed to assess the association of hemoglobin levels and leukocytes count between the two groups. A total of 144 data were collected, 54 physiological and 90 pathological hyperbilirubinemia. In physiological hyperbilirubinemia, hemoglobin levels and leukocyte counts were found to be normal, whereas in pathological anemia and leukocytosis developed and the difference between the two groups was statistically significant (p<0,001). Anemia was found in neonates with pathological hyperbilirubinemia caused by RDN, LBW, sepsis, hemolytic, and hemorrhagic. Leukocytosis was found in pathological hyperbilirubinemia caused by sepsis.There was a significant difference between the incidence of anemia and leukocytosis in physiological and pathological hyperbilirubinemia. It can be concluded that routine blood tests can be used to distinguish whether hyperbilirubinemia experienced by neonatel patient is a physiological or pathological condition, so it can be one of the tests suggested when the neonate is hyperbilirubinemia.